A spirituality of listening : living what we hear - Anderson, Keith, 1949- (IVP Books, an imprint of InterVarsity Press, 2016)
God is speaking in our everyday world. How can we become more attuned to listening for God's voice? Keith Anderson walks us through key biblical themes that help us to see and experience how God is present with us if we would only listen.